CO-INFECTION OF BRUCELLA AND DENGUE VIRUS - Dutta, Devarati; Kuila, Prabir; Chatterjee, Debasmita; Das, Satadal (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Brucellosis is an important zoonotic infection having a worldwide distribution. In South East Asian developing countries like India, brucellosis is yet well-known but often neglected disease. Although dengue fever has a global distribution, South East Asian region together with the Western Pacific region represents 75% of the current global disease burden. Frequent dengue fever outbreaks have been encountered in different parts of India. Both brucellosis and dengue fever may present with many nonspecific symptoms. This study was designed to identify the trend of their co-infection. Methods: The study was carried out from February 2015 to July 2016 in Eastern India. Blood samples collected from clinically suspected dengue fever cases were confirmed serologically by dengue specific NS1, IgM, and IgG capture ELISA methods. The confirmed dengue samples were further subjected to Brucella specific serological and molecular investigations. Results: Out of 37 serologically confirmed dengue cases, 8 (21.6%) showed co-infection of brucellosis and dengue fever. Female predominance was observed among the co-infection cases. Most of these cases belonged to the age group 21-40 years and resided in and around Kolkata. Conclusion: This study portrays the simultaneous acquisition of these two pathogens in a few patients. Co-infection of these two pathogens, while feasible, has not been accounted previously in this part of India. Thus, this report highlights the significance of studying the possibility of occurrence of dual infection of these two diseases and its outcome in patients with febrile illness thereby providing future scope of preventing case fatalities Keywords: Brucellosis, Dengue, Co-infection, ELISA, Polymerase chain reaction.